Impact of CSR on firm performance: The moderating role of family ownership in individualistic & collectivistic countries - Abhishek Omprakash Singh (Junior Management Science (JUMS), 2024)
The objective of this study is to have a cross-country examination of the moderating role of family ownership on the corporate social responsibility (CSR) - financial performance (FP) relationship, also understanding how the moderating effect is influenced by cultural dimensions of collectivism and individualism. The study thereby incorporates views from both the Stakeholder theory and the Institutional theory. The study employs the one-way fixed effects regression analysis. Firm-year observations for the period of 2013 to 2022 of 439 firms across 35 countries are included. The magnitude of the interaction term is then inspected across the deemed collectivistic and individualistic cultures. The study finds that the degree of family ownership positively moderates the CSR-FP relationship and this moderation effect is stronger for collectivistic countries. The study is a novel approach to taking the CSR-FP subject with the family ownership moderating effect in a cross-country setting and it uniquely measures family ownership, not as the usual binary or subjective construct. The results of the study yield an interesting insight on the appropriate ownership structure for family members, and the status of legitimacy and trust family businesses can leverage with CSR to improve FP.
Keywords: 330; collectivism; corporate social responsibility (CSR); family ownership; financial performance (FP); individualism